The Rise of the Free Movements: How Posting Shapes a Hybrid Single European Labour Market - Ninke Mussche; Vincent Corluy; Ive Marx (Institute for the Study of Labor (IZA), 2016)
Intra-EU mobility has been the subject of debate from its very inception. Some scholars argue that intra-EU labour migration improves the allocation of human capital in the EU and contend that the level of permanent-type labour mobility is still too low to talk of a single European labour market. Others point to the social downside of both free labour mobility and free service mobility, such as the increased precariousness of industrial relations, and problems of wage dumping. Since the downsides are acute and demand attention, less attention has been given to the origins, destinations and nature of the posting flows more generally. One of the reasons for this is the fact that data on posting are still scarce. This article aims to fill this gap by exploring unique posting data for Belgium. Based on these data we argue that while the free movement of labour and a single European labour market has been a policy goal for decades, it is the free movement of services that is well on its way to shape a hybrid single European labour market. Permanent type mobility is greatly complemented with high levels of short term service mobility. Service mobility/posting is as much a phenomenon of intra-EU15 mobility, than it is of EU12 mobility. Moreover, posting is set to remain more popular than classical free movement of labour among EU12 citizens. Service workers circumvent the most important linguistic, cultural, institutional and social hurdles that classical mobile workers face in a diverse EU. The free movement of services is developing to such an extent that it complements permanent type free labour mobility in shaping a single but typically European labour market that is driven by diversity and circular mobility.
Keywords: J61; 330; posting; migration; labor mobility